Surgical clipping or endovascular coiling for unruptured intracranial aneurysms: a pragmatic randomised trial. Issue 8 (20th June 2017) - Darsaut, Tim E; Findlay, J Max; Magro, Elsa; Kotowski, Marc; Roy, Daniel; Weill, Alain; Bojanowski, Michel W; Chaalala, Chiraz; Iancu, Daniela; Lesiuk, Howard; Sinclair, John; Scholtes, Felix; et al.
Abstract : Background: Unruptured intracranial aneurysms (UIAs) are increasingly diagnosed and are commonly treated using endovascular treatment or microsurgical clipping. The safety and efficacy of treatments have not been compared in a randomised trial. How to treat patients with UIAs suitable for both options remains unknown. Methods: We randomly allocated clipping or coiling to patients with one or more 3–25 mm UIAs judged treatable both ways. The primary outcome was treatment failure, defined as: initial failure of aneurysm treatment, intracranial haemorrhage or residual aneurysm on 1-year imaging. Secondary outcomes included neurological deficits following treatment, hospitalisation >5 days, overall morbidity and mortality and angiographic results at 1 year. Results: The trial was designed to include 260 patients. An analysis was performed for slow accrual: 136 patients were enrolled from 2010 through 2016 and 134 patients were treated. The 1-year primary outcome, available for 104 patients, was reached in 5/48 (10.4% (4.5%–22.2%)) patients allocated surgical clipping, and 10/56 (17.9% (10.0%–29.8%)) patients allocated endovascular coiling (OR: 0.54 (0.13–1.90), p=0.40). Morbidity and mortality (modified Rankin Scale>2) at 1 year occurred in 2/48 (4.2% (1.2%–14.0%)) and 2/56 (3.6% (1.0%–12.1%)) patients allocated clipping and coiling, respectively. New neurological deficits (15/65 vs 6/69; OR: 3.12 (1.05–10.57), p=0.031), and hospitalisations beyond 5 days (30/65 vs 6/69; OR: 8.85 (3.22–28.59), p=0.0001) were more frequent after clipping. Conclusion: Surgical clipping or endovascular coiling of UIAs did not show differences in morbidity at 1 year. Trial continuation and additional randomised evidence will be necessary to establish the supposed superior efficacy of clipping.